PW 2049 Review of a national water safety and drowning prevention model three years on: a sri lankan case study. (November 2018) - Birch, Rhiannon; Dhamaratne, Samath D; Matthews, Bernadette; Wijayaratne, Sanath; Nanayakkara, Asanka; Jayawardena, Mevan
Abstract : Drowning is the second highest cause of accidental death in Sri Lanka, with a rate of 4.4 deaths per 1 00 000 population. Whilst drowning prevention has been on the injury prevention agenda in high income countries (HICs) over a number of years, many low and middle income countries (LMICs) like Sri Lanka are working towards drowning prevention and seeking support from those in government, private sector and community settings. Best practise models from HICs can be adapted and applied by those in LMICs. Conversely, there are models from LMICs, particularly based on innovation, which can be adapted for HICs. Sri Lanka Life Saving has long been working towards a water safe Sri Lanka. In partnership with Life Saving Victoria, a national model for water safety and drowning prevention was developed and formally implemented in 2015. This model was based on internationally accepted injury prevention models and drowning prevention strategies. We outline the key steps and specific examples in the model along with key outputs. Key outputs included: internationally recognised lifesaving training delivered to Sri Lankan personnel across various industries including tourism, swimming, lifesaving and the armed forces; expansion of lifesaving services utilising armed forces personnel previously involved in the civil conflict; partnerships developed with government, industries and non-profit organisations; publication of the first Drowning Prevention Report for Sri Lanka; the Sri Lankan Drowning Prevention and Water Safety Plan developed with a multi-stakeholder governance and implementation structure; and the Swim for Safety program educating over 2000 children in survival swimming and water safety. The outputs from the water safety and drowning prevention model have helped increase the profile and elevate the importance of developing lifesaving and drowning prevention activities within Sri Lanka. This model provides a guide for other practitioners to develop and structure comprehensive drowning prevention initiatives.